(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The main focus of the construction industry is to ensure that projects are successfully completed within the constraints of best quality, stated period and at minimum cost possible. The implementation of Quality Control System in Construction Industry is meant to assist the industry to improve the efficiency and effectiveness of the organization management system in ensuring successful objectives of company. In the area of globalization where economic competition is intensifying, the implementation of Quality Control System will improve the overall construction process and subsequently lead to the formulization of successful business strategies to meet international requirements. But the main problem with quality control system implementation in construction industry is that the check parameter is not easy to understand for employees.The quality parameters should easy to understand specially checklists should be easy to understand and easy for implementation In this study is carried out to analyze the scenario of QC ( Quality Control) System application, to identify factors affecting the construction organization and to issue recommendations on how to improve the implementation of QC System in Construction Industry. Initially the checklists are observed from different site the defects will identify in check lists and suggest new checklists for each items of construction. By taking suitable case study modify checklists are implemented and observe the difference in quality in terms of time and money.